L’assurance de carence, dite « difference in conditions » - Moreau, Rémi (Assurances, 1985)
This time, Me Rémi Moreau explores the insurance coverage known as the "difference in conditions". He mentions the implications and restrictions of a policy which can vary, but are in any case indisputably interesting, if adapted to the needs of the Insured.